TUNTUNAN AL QURAN MENGENAI PEMBINAAN TOLERANSI MELALUI KOMUNIKASI PADA ANAK DI KELUARGA - Waway Qadratulloh (Universitas Negeri Medan, 2018)
ABSTRACT The rise of intolerance, violence, bullying, extreme and radical actions in social life in society can not be separated from how the pattern of education and communication patterns in the family environment. In fact, in fact the Qur'an has led to his people to build a family that can pass on the good in it. This is in line with marriage as part of worship that has a function to keep maqashid al shari'ah..This article discusses the guidance of the Qur'an in communicating with children in the family environment. The established communication pattern is communication that can instill tolerant attitude on the child to be applied in individual life and social. There are six communication patterns that are guided in the Quran, namely qaulan baligha, qaulan sadida, qaulan karima, qaulan maysura, qaulan ma'rufa, and qaulan maysura. The six communication patterns are characteristic of Rabbani, Humane, Universal, Balanced, and Realistic.Keywords: communication, tolerance, guidance of the Qur’an